2015
DOI: 10.1093/cid/civ791
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin Resistance in Candida

Abstract: Invasive fungal infections are an important infection concern for patients with underlying immunosuppression. Antifungal therapy is a critical component of patient care, but therapeutic choices are limited due to few drug classes. Antifungal resistance, especially among Candida species, aggravates the problem. The echinocandin drugs (micafungin, anidulafungin, and caspofungin) are the preferred choice to treat a range of candidiasis. They target the fungal-specific enzyme glucan synthase, which is responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
218
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(237 citation statements)
references
References 77 publications
(95 reference statements)
6
218
0
1
Order By: Relevance
“…It is well known that echinocandin clinical resistance is linked to FKS hot spot substitutions (5). The 32-fold increases in echinocandins MICs observed for the seven chimeric S. cerevisiae mutants support the assumption that L633M and T634A polymorphisms at C. guilliermondii Fks1p hot spot 1 are responsible for the observed RES in this species.…”
Section: Table 1 Primers Used In This Studysupporting
confidence: 63%
See 3 more Smart Citations
“…It is well known that echinocandin clinical resistance is linked to FKS hot spot substitutions (5). The 32-fold increases in echinocandins MICs observed for the seven chimeric S. cerevisiae mutants support the assumption that L633M and T634A polymorphisms at C. guilliermondii Fks1p hot spot 1 are responsible for the observed RES in this species.…”
Section: Table 1 Primers Used In This Studysupporting
confidence: 63%
“…Echinocandin drugs interact with the Fksp subunits of the ␤-1,3-glucan synthase complex, inhibiting the biosynthesis of the principal cell wall glucan. Clinical resistance was linked to hot spot mutations in Fksp (5). It was molecularly confirmed that the C. parapsilosis sensu lato RES phenotype is due to a naturally occurring substitution (P660A) in the hot spot 1 region of Fks1p (8).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…T reatment with echinocandins, i.e., caspofungin, micafungin, and anidulafungin, is recommended as the primary therapy for patients with candidemia (1,2). Rates of resistance are low (3), but attenuation of activity at high concentrations, known as the paradoxical or Eagle effect, has been reported (4)(5)(6)(7).…”
mentioning
confidence: 99%